Successful Management of Acquired Hemophilia A Associated with Bullous Pemphigoid: A Case Report and Review of the Literature - Quentin Binet; Catherine Lambert; Laurine Sacré; Stéphane Eeckhoudt; Cedric Hermans (Case Reports in Hematology)
Background. Acquired hemophilia A (AHA) is a rare condition, due to the spontaneous formation of neutralizing antibodies against endogenous factor VIII. About half the cases are associated with pregnancy, postpartum, autoimmune diseases, malignancies, or adverse drug reactions. Symptoms include severe and unexpected bleeding that may prove life-threatening. Case Study. We report a case of AHA associated with bullous pemphigoid (BP), a chronic, autoimmune, subepidermal, blistering skin disease. To our knowledge, this is the 25th documented case of such an association. Following treatment for less than 3 months consisting of methylprednisolone at decreasing dose levels along with four courses of rituximab (monoclonal antibody directed against the CD20 protein), AHA was completely cured and BP well-controlled. Conclusions. This report illustrates a rare association of AHA and BP, supporting the possibility of eradicating the inhibitor with a well-conducted short-term treatment.